SignTalk: An Assistive Bi-Directional Real-Time Sign Language Mobile Application using MediaPipe, CNN, and GAN - Abalos, Diane Marie M; Dacsil, John Chrismark B; Raquedan, Ainah Angeline L (LPPM STIKI Malang, 2024)
In the realm of inclusive education, the hearing-impaired community often faces communication barriers, particularly in educational settings where sign language may not be universally understood. This research study endeavors to address this issue through the development of a bi-directional sign language application tailored to the unique needs of hearing-impaired students, parents, and teachers at Paete Elementary School. Before this research, no dedicated studies or applications have been crafted yet. Employing a quantitative approach via simple random sampling as the instrumentation for the client's population, this study aims to delve into the participants' perspectives. This pioneering initiative provides valuable insights into technology-driven solutions for the communication gap in education for the hearing-impaired. Its findings are poised to significantly contribute to inclusive education and technology-assisted learning, fostering a more accessible educational environment for the hearing-impaired community. The researchers strongly encourage future studies to prioritize technological solutions that cater explicitly to the diverse needs of Special Education (SPED) students or Persons with Disabilities (PWD). Understanding their requirements and challenges is crucial in creating more inclusive and effective applications or tools. Further with research studies understanding their requirements and challenges is important in creating more inclusive and effective applications or tools. Foster interdisciplinary collaborations between technology experts, educators, therapists, and specialists in the field of disability studies. Collaborative efforts can yield comprehensive solutions that integrate technological advancements. KeywordsHearing Impaired Individuals, Sign Language, Sign Talk, Special Education *Correspondence Email:author@email.com